Characteristics of Some Agronets in Visible Range - Sharan, Girja; Chitlange, Vishaka (Journal of Agricultural Engineering, 2004)
Agronets are knitted fabric made out of UV stablised (HDPE) plastic. These are mechanically strong and light in weight. Nets are widely used to shade greenhouses, nurseries, etc. Several manufacturers now supply agronets. Suppliers indicate the shading percentage of each net to facilitate selection by the user. Shading percentages commonly available are 85%, 75%, 60% and 50%. For each shading percentage there is choice of colours-black, white, green, blue and combinations. A sample-of nets obtained from the market were tested for their shading characteristics. Need for the tests was felt while selecting a suitable net to shade a greenhouse at Kothara (Kutch), an extremely arid and hot region.